(untitled) (Media Kesehatan Masyarakat Indonesia, 2018)
There is limited information regarding the behavior and determinant factors of non-prescribed use of antibioticsin Surabaya. The purpose of this study was to identify the behavior and the most influential factors in using antibiotics without prescription. This was a cross sectional studyconducted insubjects who bought antibiotics without prescription in 90 pharmacies in Surabaya during December 2014-April 2015. Eight complex questions were used to identify the behavior. The contributing factors of non-prescription behavior were identified by using two statistical methods, including: descriptive analysis by comparing the mean of the questions in each factor theme, and factor analysis using orthogonal rotation (varimax). There were 267 respondents involved in this study. The majority of respondents who bought antibiotics without prescription ranged from age 21-30 years old (36.33%), frequency buying antibiotics 1/month (45.70%), intended for themselves (56.55%), buying antibiotics soon after the symptoms appeared (33.70%), and intended for runny nose/flu indication (21.30%). Based on the descriptive statistic, the theme “aspects that encourage” was found as the factor contributed to the use of antibiotics without prescription. The value of cumulative percent total variance found in the factor analysis method explained was 48.03%, with the biggest value on the first factor that was 23.91%. The most influential factor was the ease of access to get the antibiotics and the saving of money. The results of this study can be used to determine the appropriate intervention to deal with the use of antibiotics without prescription in the pharmacies.Considering the complex causes of such behavior, pharmacist should not be blamed as the only cause of non-prescribed use of antibiotics.